DEVELOPING COMMUNICATIVE COMPETENCE OF YOUNG LEARNERS THROUGH GAME-BASED LEARNING TECHNOLOGIES - Samanova Shakhlo Bakhtiyarovna (Journal of Applied Science and Social Science, 2026)
This study describes the effectiveness of game-based learning technologies in developing communicative competence among young learners. In contemporary language education, fostering learners’ ability to use language meaningfully in real-life contexts is a central objective. Game-based learning provides an interactive and motivating environment that encourages active participation, reduces anxiety, and promotes spontaneous language use. The study is grounded in sociocognitive and communicative approaches, emphasizing the role of social interaction and meaningful communication in language acquisition. Through the integration of digital and traditional didactic games, learners engage in collaborative tasks that enhance their speaking skills, vocabulary, and pragmatic competence.